Seismic Risk Assessment and Rehabilitation Method of Existing RCC Structures Using Micro Concrete - Jijing Yin; Debao Tang; Ting Chen; Yang Yang; Ling Ju; Yu Wan; Junpeng Ma; Xianqiang Yue (Salehan Institute of Higher Education, 2023)
Aging reinforced concrete (RC) building structures typically experience more severe damage and are prone to collapse during earthquakes, constituting a primary factor in casualties and direct economic losses. To enhance the seismic performance of these old structures, this paper proposes a seismic risk assessment and a micro-concrete restoration method. It applies the process to an existing three-story reinforced concrete structure. A practical framework for mitigating structural vulnerabilities in seismic-prone regions was proposed. Then an as-built survey was conducted to create as-built architectural and structural drawings. Concrete core tests, ferroscans, and rebar tests were also performed. Based on field surveys and test data, nonlinear static and dynamic analyses have been used to evaluate structural safety. Concrete column jacketing was used to strengthen weak existing columns with micro-concrete. In assessing the structural response of retrofitted buildings, a comparison was made to their initial state. The comparison shows that applying concrete column jacketing with micro concrete can reduce other structural elements' demand capacity ratio (DCR), minimize maximum displacements, and enhance overall stiffness. The results indicate that the proposed method effectively evaluates the seismic risk of aging structures and enhances seismic resilience in existing buildings. Moreover, the application to the actual structure demonstrates that micro-concrete is highly durable and compatible with parent-concrete. Doi: 10.28991/CEJ-2023-09-12-04 Full Text: PDF